The Role of Tenure on The Relationship Between Job Autonomy and Job Involvement Among Senior High School Teachers in Private Schools - Olievia Prabandini Mulyana; Umi Anugerah Izzati; Miftakhul Jannah (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Teachers have a crucial role in the context of education. Teacher productivity relates to the extent of teacher involvement in their work. This study aimed to determine the role of tenure in the relationship between job autonomy and work involvement of high school teachers. Method: This study uses quantitative research with cross-sectional methods. The subjects in this study amounted to 75 high school teachers in private schools. The research instrument uses two forms of scale, namely, the scale of job autonomy and the scale of work involvement. Data collection using SPSS process Moderation Model 1. Results: Results show the role of tenure moderation in job autonomy and work engagement. The correlation of positive research shows that the longer the working period, the more strengthening the relationship between job autonomy and work engagement. Novelty: This study shows the role of tenure as a moderator on the relationship between job autonomy and job engagement in high school teachers in private schools.